Using CAT Tools in Freelance Translation insights from a case study - Pietrzak, Paulina 1984-; Kornacki, Michał 1982- (Routledge, 2021)
This book explores the impact of applying computer-assisted (CAT) tools in freelance translation toward better understanding translators' strategies, preferences, and challenges in using new technologies and identifying areas of enhancement in translator training. The volume offers a brief overview of the latest developments in technology in translation, examining such issues as the effect on the translation process and the dynamics of the translator-technology interaction. Drawing on data from a study with active translators in Poland, Pietrzak and Kornacki examine the underlying factors underpinning translators' lack of engagement with these tools, including such issues as prevailing pre-conceptions around technology and limited knowledge hindering the most efficacious use of these resources and the subsequent impact on translator identity. Taken together, the book brings together these insights to help pinpoint freelance translators' needs more effectively and adapt training programmes accordingly. The volume will be of interest to scholars in translation studies with an interest in process and technology as well as active translators
"Routledge focus"
Description based on online resource; title from digital title page (viewed on January 20, 2021)
Keywords: Translating and interpreting / Data processing